Effect of flame spray deposition parameters on the microstructure of Al2 O3 - 13 %TiO2 coatings applied onto 7075 aluminum alloy (2018)
ABSTRACT: In this work, the effect of flame spraying parameters on physical, structural and microstructural characteristics of Al2O3 - 13 wt.% TiO2 (AT-13) coatings were studied. NiCrAl and AT-13 feedstock powders were used for spraying a bond coat (BC) and a top coat (TC), respectively, onto a 7075 aluminum alloy substrate. The effect of acetylene-to-oxygen ratio and the spraying distance on surface roughness, crystalline phases, porosity and thickness of top coat were analyzed. The results showed that for the evaluated spraying conditions, the volumetric oxy-fuel ratio had significant effects on roughness, porosity and crystalline phases of the coating. On the other hand, the spraying distance affected the thickness of the coating and did not influence the formation of Al2TiO5 phase; no significant effect of spraying distance on roughness was observed. The results showed that an acetylene: oxygen volumetric ratio of 1:2.5 is preferable to obtain higher melting of the ceramic powders and therefore a denser coating with major content of γ-Al2O3 crystalline phase.